La Medicina Basada en la Evidencia: ¿mejoró la medicina que practicamos y enseñamos? - Huicho, Luis (2013)
The concept of evidence-based medicine (EBM) has been increasingly incorporated in medicine practice and teaching. In the clinical arena it is defined as the use of the best available scientific evidence coming from clinical research for decision-making purposes, when facing individual patients. This paradigm change in the way medicine is taught and practiced has been due in part to the accelerated progress in scientific research, particularly in the last few decades, albeit the increasing costs involved in care of patients also played an important role in its development and consolidation. EBM involves integration of clinical expertise with the available external evidence, and provides a more critical approach to clinical problems, reducing error probabilities in different phases of the clinical process. It is not easy to reach a definitive conclusion about its impact on teaching and practice of medicine in our setting, due to the lack of systematic impact research in this area. At global level, we undoubtedly have available greater scientific evidence now, including the child health field. These scenarios, along with the amazing technological advances we are witnessing allow us to use relevant bedside clinical information. However, if we are really looking for a better medicine based on sound information but also on genuine respect to health as a basic human right, we should intensify our efforts to break once and for all with the paradigm of an authoritarian medicine, suspicious of any dissent, and reluctant to justify adequately any clinical decision made. We should additionally take advantage of the highly improved access to scientific information, and we should be willing to share such justifications with our patients in a friendly and respectful way. Similarly, we badly need to actively promote research, creativity and critical thinking at all educational levels, so we can make a real and significant contribution to the advancement of clinical medicine and public health.